A wearable antenna based on fabric materials with circular polarization for Body-centric wireless communications - Adel Y. I. Ashyap; Z. Z. Abidin; Samsul Haimi Dahlan; Shaharil Mohd Shah; Huda A. Majid; Yee See Khee; Norun Abdul Malek (Institute of Advanced Engineering and Science, 2020)
A compact and simple structure antenna for wearable application at 2.4 GHz is presented and studied. The felt fabric material is used in this paper due to its suitable thickness and dielectric constant. This material provides high flexibility which can be easily worn on a body and incorporated into our daily clothes. In view of the fact that the design will work on a moving person, therefore a circularly polarized antenna is desired to optimize the off-body communication link. The Cicular Polarization (CP) is achieved by introducing truncated corners on the patch. The antenna size is 60 × 60 × 2 mm3. The Axial Ratio (AR), the Front to Back Ratio (FRB) and the realized gain are 0.96 dB, 10.5 dB, and 4.62 dB, respectively indicating a good performance of the antenna at the desired frequency. Furthermore, the antenna was investigated when operating near the body. The obtained result shows that the design has performance similar to the case of free space. This is due to the present of the full ground plane that acts as a shielding between the antenna and body. Finally, the Specific Absorption Rate (SAR) is carried out and showed that the antenna has a level less than the limits fixed by the FCC standard. Therefore, the antenna could be useful for wearable applications.